The Effects of Experimentally Manipulated Social Status and Food Insecurity on Acute Eating Behavior and Risk for Obesity Among Adolescents: A Randomized Controlled Study (P21-058-19). (13th June 2019) - Cardel, Michelle; Pavela, Gregory; Janicke, David; Dulin, Akilah; Huo, Tianyao; Miller, Darci; Lee, Alexandra; Piff, Paul; Gurka, Matthew; Dhurandhar, Emily; Peters, John; Caldwell, Ann; et al.
Abstract: Objectives: Subjective and objective social status is associated with weight status, but this relationship differs by sex and the mechanisms remain unclear. Methods: This randomized study in Hispanic adolescents investigated the effects of experimentally manipulated social status on ad libitum acute and 24-hour dietary intakes and stress-related outcomes as potential mechanisms through which social status affects weight. Participants ( n  = 133; ages 15–21; 60.2% girls; BMI ≥18.5 and ≤40 kg/m 2 ; 23.4% food insecure) consumed a standardized breakfast and then were randomized to a low (LOW) or high social status position (HIGH) in a rigged game of Monopoly™, in which the rules differed substantially by social status position. Following the game, the participants consumed an ad libitum lunchtime meal. Energy intake was assessed by pre- and post- food weighing. Stress-related markers were measured at baseline, before Monopoly™, after Monopoly™, and after lunch, with the exception of cortisol (measured before and after Monopoly™). Results: There was a significant interaction between sex and experimentally manipulated social status ( P  = 0.0087), such that girls randomized to LOW consumed significantly more of their daily energy needs at the ad libitum lunchtime meal relative to those randomized to HIGH (37.5% vs. 34.3%, respectively). Individuals with food insecurity consumed a greater % of their daily energy needs at the lunchtime meal than those with food security, although the result was not quite statistically significant (40.7% vs. 36.3%, respectively; P  = 0.08). In LOW, participants report decreased feelings of powerfulness following Monopoly™ ( P  = 0.0006). There were no significant differences between HIGH and LOW following Monopoly™ regarding perceived stress, cortisol, heart rate, or blood pressure. Social status condition was not related to 24-hour % of daily energy needs consumed. Conclusions: Our data suggest a causal link between experimentally manipulated low social status and increased acute energy intakes among Hispanic girls, potentially influenced by decreased feelings of powerfulness, which is independent of stress. Low social status may play a causal role in the development of obesity by promoting excess calorie consumption. Further research is needed to identify the biobehavioral mechanisms contributing to this phenomenon. Funding Sources: NIH. Supporting Tables, Images and/or Graphs: